Taxus wallichiana (Himalayan Yew) for the Livelihood of Local People in Some Protected Areas of Nepal - Gajurel, Jyoti Prasad; Shrestha, Krishna Kumar; Werth, Silke; Scheidegger, Christoph (Journal of Natural History Museum, 2015)
Nepal is a small country but diverse in ethnic communities living in different parts of the country. These ethnic communities have been practicing the indigenous knowledge of plants for their livelihood. The objective of this study is to document the traditional knowledge of one of the most important medicinal plant species Taxus wallichiana Zucc. in different altitudinal gradients in Manaslu Conservation Area, Sagarmatha National Park and surrounding and Kanchenjunga Conservation Area. This study was carried out in six altitudinal gradients (2200 m asl to 3800 masl) with altitudinal steps of 400 m asl. We used direct observation method and standardized interviews to collect the data related to the use of T. wallichiana. Out of five caste groups, only four were local to the site while one cast had migrated from Terai region and had settled down recently. The four caste groups included Sherpa, Tamang, Rai and Gurung who have been using the plant products for various reasons. People used the species as timber, medicine for jaundice and cancer, fence, construction material for houses and cattle fodder. Knowledge of the use of T. wallichiana was mainly available at an altitude of 2600 m a.s.l., the species altitudinal distribution optimum. Most of the informants were related to community forests in the study areas and many also depend on plants for their livelihood. This study also helped the local people by informing them about sustainable use and conservation of this plant in the study areas. J. Nat. Hist. Mus. Vol. 28, 2014: 1-8